2008
DOI: 10.1027/1015-5759.24.4.226
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing the Implicit Association Test Increases Explicit Evaluation of Target Concepts

Abstract: Abstract.In an effort to remove a presumed confound of extrapersonal associations, Olson and Fazio (2004) introduced procedural modifications to attitude versions of the Implicit Association Test (IAT). We hypothesized that the procedural changes increased the likelihood that participants would explicitly evaluate the target concepts (e.g., rating Black and White faces as liked or disliked). Results of a mega-study covering 58 topics and six additional studies (Total N = 15,667) suggest that: (a) after persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 17 publications
0
37
2
1
Order By: Relevance
“…Hofmann et al 2005) and research into the influence of different varieties of the IAT with respect to the outcomes measured. For example, it has been found that a slightly changed "personalized" IAT assessed in somewhat different associations than the "standard" IAT (Houben and Wiers 2007;Nosek and Hansen 2008;Olson and Fazio 2004). By implication, it is likely that the IAT which used pictures from the bullying movie (i.e., the pictures are likely to have acquired personal emotional meaning due to the movie) assessed something different from the general IAT which assesses associations with the general concept of bullying (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hofmann et al 2005) and research into the influence of different varieties of the IAT with respect to the outcomes measured. For example, it has been found that a slightly changed "personalized" IAT assessed in somewhat different associations than the "standard" IAT (Houben and Wiers 2007;Nosek and Hansen 2008;Olson and Fazio 2004). By implication, it is likely that the IAT which used pictures from the bullying movie (i.e., the pictures are likely to have acquired personal emotional meaning due to the movie) assessed something different from the general IAT which assesses associations with the general concept of bullying (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nosek and Hansen (2008) argued, using data collected from an IAT web site, that respondents to the personalized IAT are more likely than those completing the standard IAT to mistakenly evaluate the target category exemplars in terms of attributes. That is, respondents were argued to sometimes classify targets (Black and White exemplars) in terms of like/dislike instead of by race in accordance with the instructions.…”
Section: The Present Researchmentioning
confidence: 99%
“…Because there are controversies surrounding which IAT is optimal for assessing automatic evaluations (e.g., Gawronski, Peters, & LeBel, 2008;Han, Czellar, Olson, & Fazio, 2010;Han, Olson, & Fazio, 2006;Nosek & Hansen, 2008a, 2008bOlson & Fazio, 2004;Olson, Fazio, & Han, 2009), Experiment 3 utilized the standard IAT to extend the findings from Experiments 1 and 2. Although we expected the effects of perspective taking on the two IAT variants to be comparable, it is ultimately an empirical question.…”
Section: Experiments 3: Automatic and Deliberate Interracial Evaluatiomentioning
confidence: 99%